Нові правила виробництва, маркування та обігу органічної продукції - Боснюк-Григор’єва, Ю.; Bosniuk-Hryhorieva, Yu. (Східноєвропейський національний університет імені Лесі Українки, 2019)
В статті проаналізовано основні положення Закону України «Про основні принципи та вимоги до органічного виробництва, обігу та маркування органічної продукції», який набув чинності 02.08.2019 р., зокрема, вимоги до виробництва, контроль за виробництвом (сертифікація) та відповідальність за недотримання відповідних вимог. В статті окреслено значення найпоширеніших видів маркувань «біо», «еко», «органік». Наголошено на зростанні рівня гігієнічних вимог та стандартів безпечності харчових продуктів на світовому ринку, що зумовлює необхідність впровадження світових стандартів обігу органічної продукції на законодавчому рівні в Україні.The article highlights the main provisions of the law «On the basic principles and requirements for organic production, circulation, and labeling of organic products» in Ukraine. The author substantiates the requirements for production, production control (certification), and defines the responsibilities for noncompliance with the requirements. The requirements for the most common types of labeling «bio», «eco», «organic» are described. The emphasis is laid on the benefits of meeting the high standards of the organic product quality, which is a ground for the introduction of the world trends regarding the circulation of organic products and active support of it at the legislative level in Ukraine. The new law not only raises the standards of production of organic products, which is a positive phenomenon, but also increases the burden on the national producer. The results of the study show that compliance with the Law of Ukraine "On Basic Principles and Requirements for Organic Production, Circulation, and Labeling of Organic Products" extends the target market for agricultural products to the producer and simplifies the procedures for its export to other countries.
New Rules for Production, Labeling and Circulation of Organic Products
Keywords: органічна продукція; сертифікація органічної продукції; маркування «біо»; «еко»; «органік»; адміністративна відповідальність; organic products; certification of organic products; labeling «bio»; «eco»; «organic»; administrative responsibility